RETINAL ARTERIOLAR STRUCTURE IN PRIMARY HYPERTENSION – REVIEW OF THE DATA - Andrzej Januszewicz (Artery Research, 2015)
Vascular dysfunction and remodelling due to elevated blood pressure constitutes an early step in the pathogenesis of atherosclerotic disease. Microvascular remodelling reduces tissue perfusion and impedes blood-tissue exchange. These processes could lead to inadequate perfusion and tissue hypoxia in situations of high metabolic demand. Impaired tissue perfusion may be involved in target-organ damage and complications that involve several vascular beds. Of all of these organs, the retina represents an open and easily accessible window for the in vivo study of human microcirculation. Recently a new approach focused on retinal-arteriolar structural parameters by using scanning laser Doppler flowmetry (SLDF) with automatic full-field perfusion imaging analyses has been introduced. By means of SLDF it is possible to reliable assess the structural parameters of the retinal arterioles. In studies based on SLDF technique it has been shown that blood pressure is an independent determinant of wall-to-lumen ratio of retinal arterioles. It was also demonstrated that wall-to-lumen ratio correlates with urinary albumin excretion. It was shown that patients with better blood pressure control had significantly lower wall-to-lumen ratio than patients with worse blood pressure control. Recently it has been also shown that Our data indicate treatment with aliskiren, direct renin inhibitor, improves altered vascular remodelling of retinal arterioles in hypertensive patients. In summary, evaluation of retinal arteriolar structure, enables not only to assess early organ damage in patients with hypertension but also to assess the effect of hypertension treatment on small arteries remodelling in vivo.